2020
DOI: 10.1093/infdis/jiaa742
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Transmission of SARS-CoV-2 and Other Respiratory Viruses: A Systematic Review

Abstract: Background While risk of outdoor transmission of respiratory viral infections is hypothesized to be low, there is limited data of SARS-CoV-2 transmission in outdoor compared to indoor settings. Methods We conducted a systematic review of peer-reviewed papers indexed in PubMed, EMBASE and Web of Science and pre-prints in Europe PMC through August 12 th, 2020 that described cases of human transmission of SARS-CoV-2. Reports of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
237
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(281 citation statements)
references
References 34 publications
10
237
1
3
Order By: Relevance
“…Individuals working outside and in the fields were more likely to be both currently infected and seropositive, respectively. Whereas indoor exposures are thought to be associated with the greatest risk of transmission, 19 a lower perceived sense of risk during outdoor work, difficulty using PPE while engaged in physically demanding tasks, or socioeconomic differences among outdoor and indoor workers may contribute to the observed association in our study. While the estimated risk ratio for infection associated with workplace exposure was lower than that for household exposure, this difference could in part reflect misclassification, if individuals are are more likely to know about the health of household members.…”
Section: Discussionmentioning
confidence: 65%
“…Individuals working outside and in the fields were more likely to be both currently infected and seropositive, respectively. Whereas indoor exposures are thought to be associated with the greatest risk of transmission, 19 a lower perceived sense of risk during outdoor work, difficulty using PPE while engaged in physically demanding tasks, or socioeconomic differences among outdoor and indoor workers may contribute to the observed association in our study. While the estimated risk ratio for infection associated with workplace exposure was lower than that for household exposure, this difference could in part reflect misclassification, if individuals are are more likely to know about the health of household members.…”
Section: Discussionmentioning
confidence: 65%
“…According to Dabisch et al, temperature, simulated sunlight, and humidity are among significant factors affecting the infectious SARS-CoV-2 durability in aerosols (Dabisch et al, 2020). Additionally, in enclosed spaces, low humidity, air conditioning, and low UV light may cause viral aerosol to survive longer (Bulfone et al, 2020). Results from this study indicated that the main transmission route for COVID-19 was person to person contact (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 65%
“…35 Outdoor proximity is thought to have a much lower risk of transmission than indoor proximity, with studies reporting a 19 times greater risk of transmission indoors compared to outdoors. 36…”
Section: Discussionmentioning
confidence: 99%